Singapore Method as a strategy for understanding the concept of multiplication (Revista Innova Educación, 2025)
Learning basic operations requires the integration of didactics and pedagogy as key elements in building mathematical concepts. Therefore, the objective of this article was to strengthen students’ understanding of multiplication through the design of a teaching sequence based on the Singapore Method. Considering the needs of third-grade students at Alejandro Humboldt School, a qualitative approach was adopted, complemented by descriptive analysis. A diagnostic test and a teaching sequence were designed and implemented with the participation of 20 third-grade students from the institution. The results showed that students exhibited demotivation and a lack of interest in activities involving multiplication. In addition, the results obtained from the diagnostic test and the support provided by the Milton Ochoa test highlighted the importance of strengthening their understanding. Thus, after designing and applying the teaching sequence, students developed a better understanding of multiplication. During its implementation, first, students showed willingness to solve the activities and, second, active participation in each phase of the sequence, in which they analyzed and were able to find solutions to the problem situations presented. It is concluded that the use of didactics in mathematics teaching significantly strengthens students’ learning process and, in this specific case, the Singapore Method provided dynamism and motivation as a classroom teaching strategy.
Keywords: active learning; group teaching; mathematics teaching; teaching materials; teaching method